ANALISIS PENGARUH INDEKS MODAL MANUSIA, PERTUMBUHAN EKONOMI DAN UPAH MINIMUM TERHADAP TINGKAT PENGANGGURAN TERBUKA PADA PROVINSI-PROVINSI DI INDONESIA - Meylani Cantika; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2025)
The purpose of this study is to examine how the minimum wage, economic growth, and human capital index affect the open unemployment rate in Indonesian provinces between 2019 and 2023. The open unemployment rate for the last five years is the dependent variable in this study, whereas the human capital index, economic growth, and minimum wage are the independent variables. This study uses both descriptive and associative methods. The panel data analysis model is the one that was employed in this investigation. Cross-sectional and time series data are combined in the panel data analysis approach. The Central Statistics Agency, the Ministry of Health, and the Ministry of Education and Culture provided the secondary data used in this study. The study's findings are as follows: (1) the open unemployment rate in Indonesian provinces is not significantly impacted by the human capital index; (2) the open unemployment rate in Indonesian provinces is significantly impacted by economic growth; (3) the minimum wage has no significant impact on the open unemployment rate in Indonesian provinces; and (4) the open unemployment rate in Indonesian provinces is significantly impacted by the human capital index, economic growth, and minimum wage all at the same time.